Pelindungan Hak Cipta atas Karya Ilmiah yang Dihasilkan oleh Kecerdasan Buatan - Dibit Yuniar Ekawardani; Mochamad Cholil (Jurnal Hukum Lex Generalis, 2025)
The development of Artificial Intelligence (AI) raises legal issues in copyright protection, especially for scientific works produced without human involvement. Law Number 28 of 2014 concerning Copyright does not explicitly regulate the ownership status of the work. This study uses a normative legal method to examine the legal protection of scientific works produced by AI, by examining laws and regulations and principles of intellectual property rights. The results of the study are expected to provide input for the formulation of adaptive regulations and guarantee legal certainty in the era of technological development.